Analytical and Phytochemical Exploration of Bioinsecticide Granules Mixed Betel Leaf Extract (Piper betle) and Srikaya Seed Extract (Annona squamosa) - Dhina Ayu Susanti; Ady Soesetijo; Dwi Wahyuni (Health Notions, 2018)
One alternative in controlling Aedes aegypti larvae is with the use of bioinsecticides that are environmentally friendly, safe, and inexpensive. Betel leaf and srikaya seeds contain chemical compounds that can be used as bioinsectiside. The following paper deals with detection of phytochemical in the Granules Mixed Betel Leaf Extract and Srikaya Seed using Thin Layer Chromatography (TLC) and FTIR. The TLC analysis was performed Rf value for 0.91 flavonoid compound; alkaloids 0.49; saponins 0.29 and 0.65; tannin 0.89; and anthraquinone 0.22 and 0.45. The FTIR analysis was performed represented the presence of various functional groups which includes alcohol, alkana, nitrile, and ether.Keywords: Phytochemical, Bioinsecticide, Granula, TLC, FTIR